The complex regional effects of macro-institutional change: evidence from EU enlargement over three decades - Timo Mitze; Philipp Breidenbach (Review of World Economics, 2024)
Abstract The EU enlargement process has thrust EU internal border regions into the spotlight of the European single market. This study explores how this specific macro-institutional change has impacted their socio-economic development. Tracking outcomes across four EU enlargement waves from 1986 to 2007, we identify integration effects across EU NUTS3 regions. Pooled over all waves and border regions, positive integration effects emerge for per capita GDP, labor productivity, patents per capita, and night light emissions in border regions compared to non-border areas. These effects diminish with increasing spatial distance from the enlargement border. At a detailed level, structural heterogeneities become evident across enlargement waves and region types. Internal border regions~in established EU member countries benefit relatively~in~terms of GDP per capita and labor productivity but experience relative declines in employment rates and population. In contrast, border regions in new member countries, particularly during the 2004 and 2007 eastern enlargements, gain from deepening economic integration in terms of population and employment growth. Sector-specific estimations indicate post-enlargement specialization of economic activities in border regions in line with standard trade theories.
Additional information: C23;F15;O47;R11
Keywords: 330; Economic integration; EU enlargement; Internal border regions; Regional development; Treatment effect estimation